Chrysanthemi Flos extract alleviated acetaminophen-induced rat liver injury via inhibiting oxidative stress and apoptosis based on network pharmacology analysis - Yunfeng Zhou; Chunli Wang; Jiejian Kou; Minghui Wang; Xuli Rong; Xiaohui Pu; Xinmei Xie; Guang Han; Xiaobin Pang (Taylor & Francis Group, 2021)
Context Acetaminophen (APAP) overdose is the leading cause of drug-induced liver injury. Bianliang ziyu, a variety of Chrysanthemum morifolium Ramat. (Asteraceae), has potential hepatoprotective effect. However, the mechanism is not clear yet. Objective To investigate the hepatoprotective activity and mechanism of Bianliang ziyu flower ethanol extract (BZE) on APAP-induced rats based on network pharmacology. Materials and methods Potential pathways of BZE were predicted by network pharmacology. Male Sprague-Dawley rats were pre-treated with BZE (110, 220 and 440 mg/kg, i.g.) for eight days, and then APAP (800 mg/kg, i.g.) was used to induce liver injury. After 24 h, serum and liver were collected for biochemical detection and western blot measurement. Results Network pharmacology indicated that liver-protective effect of BZE was associated with its antioxidant and anti-apoptotic efficacy. APAP-induced liver pathological change was alleviated, and elevated serum AST and ALT were reduced by BZE (440 mg/kg) (from 66.45 to 22.64 U/L and from 59.59 to 17.49 U/L, respectively). BZE (440 mg/kg) reduced the ROS to 65.50%, and upregulated SOD and GSH by 212.92% and 175.38%, respectively. In addition, BZE (440 mg/kg) increased levels of p-AMPK, p-GSK3β, HO-1 and NQO1, ranging from 1.66- to 10.29-fold compared to APAP group, and promoted nuclear translocation of Nrf2. BZE also inhibited apoptosis induced by APAP through the PI3K-Akt pathway and restored the ability of mitochondrial biogenesis. Discussion and conclusions Our study demonstrated that BZE protected rats from APAP-induced liver injury through antioxidant and anti-apoptotic pathways, suggesting BZE could be further developed as a potential liver-protecting agent.